Filling the Vacancy of the Heirs: The Reasoning of the Supreme Court's Qiyās, Certainty of the Law of Adoption in Islamic Family Law - Dita Indriani Siregar; Muchlis Bahar; Elfia; Ahmad Syukran Baharuddin (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This study critically evaluates the epistemological shift in Islamic inheritance law within contemporary Indonesian judicial practice by examining Supreme Court Decision No. 179 K/AG/1998 which employs qiyās (analogical reasoning) to grant a "Mandatory Will" for adopted children. It moves beyond descriptive accounts to interrogate whether socio-parental relations and emotional bonding can legitimately substitute nasab (lineage) as a valid legal cause (illah) within Islamic jurisprudence. Methods – Using a normative-legal approach, this research utilizes a transformative legal analysis framework. It combines standard normative legal methods with an operationalized maqāṣid al-sharī‘ah paradigm (drawing on Jasser Auda’s systems approach) and legal pluralism theories (Brian Tamanaha). Primary judicial documents and national child protection statutes are critically analyzed using thematic legal memoing and qualitative coding to assess the epistemological boundaries of judicial ijtihd. Findings – The study reveals that the Supreme Court's application of qiyās reconstructs the ontology of legal relationships by shifting the ʿillah from biological certainty to functional-protective care. While Article 209 of the Compilation of Islamic Law (KHI) provides a generic regulative basis, lower courts show significant inconsistency. This judicial disparity stems from judges constantly negotiating the tension between rigid doctrinal fidelity to classical text and the dynamic socio-legal demands of contemporary Indonesian family structures. Research implications – Theoretically, this study reconceptualizes qiyas not merely as a rigid formalistic analogical tool, but as a dynamic mechanism of legal transformation that mediates classical textual authority and contemporary empirical realities. It provides a strong epistemic justification for expanding the boundaries of family law reform through a rights-based maqāṣid lens. Originality/value – This study proposes a reconstructive analytical framework for understanding the evolution of qiyas in contemporary Islamic family law. It offers an original critique of the socio-historical constructs of classical inheritance rules, justifying how contemporary social welfare imperatives can legally reconfigure the ontology of inheritance distribution in a pluralistic legal setting.